Impact of time interval alignment on data quality in electricity grids - Schwefel, Hans-Peter; Antonios, Imad; Lipsky, Lester (Institute of Electrical and Electronics Engineers Inc., 2018)
Measurements of parameters in electricity grids are frequently average values over some time interval. In scenarios of distributed measurements such as in distribution grids, offsets of local clocks can result in the averaging interval being misaligned. This paper investigates the properties of the so-called time alignment error of such measurands that is caused by shifts of the averaging interval. A Markov model is derived that allows for numerically calculating the expected value and other distribution properties of this error. Actual consumption measurements of an office building are used to study the behavior of this time alignment error, and to compare the results from the trace with numerical results and simulations from a fitted Markov model. For increasing averaging interval offset, the time alignment error approaches a normal distribution, whose parameters can be calculated or approximated from the Markov model.
Keywords: Alignment; Clocks; Consumption measurement; Data Quality; Data quality; Distributed measurements; Distribution Grid Measurements; Distribution grid; Distribution property; Electric power transmission networks; Errors; Markov Models; Markov model; Markov processes; Mathematical model; Measurement uncertainty; Normal distribution; Numerical models; Numerical results; Office buildings; Power measurement; Smart power grids; Time Alignment Error; Time alignment; actual consumption measurements; averaging interval offset; data quality; dept.csc; distributed measurements; distribution grids; distribution properties; electricity grids; fitted Markov model; normal distribution; parameter measurement; power grids; power supply quality; power system measurement; time alignment error; time interval alignment